2009 International Conference on Game Theory for Networks 2009
DOI: 10.1109/gamenets.2009.5137385
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical spatial game over licenced resources

Abstract: Abstract-We consider a scenario in which a regulator owns the spectrum in a region. Two service providers lease spectrum from the regulator and set up a base station each to serve mobile subscribers. This leads to a hierarchical game with players at two levels-the mobile subscribers at level 1 and the service providers at level 2. In the game at level 1, each mobile subscriber chooses a service provider to subscribe to and whether to be a primary subscriber of its service provider and receive high-priority ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…First, we model the interaction between WSPs as a joint game with price and quality competitions while accounting for time-varying spectrum availability. The existing game-theoretic approaches to the dynamic spectrum market [12]- [14] have been limited to static idle channels, and to the best of our knowledge, this is the first attempt to incorporate the effect of time-varying channel availability in the game-theoretic framework. Next, we model the market dynamics as a Markov chain, and derive the Nash Equilibria (NE) of the price and quality games and the market entry barrier for each WSP.…”
Section: Wi-fi Like Servicementioning
confidence: 99%
See 1 more Smart Citation
“…First, we model the interaction between WSPs as a joint game with price and quality competitions while accounting for time-varying spectrum availability. The existing game-theoretic approaches to the dynamic spectrum market [12]- [14] have been limited to static idle channels, and to the best of our knowledge, this is the first attempt to incorporate the effect of time-varying channel availability in the game-theoretic framework. Next, we model the market dynamics as a Markov chain, and derive the Nash Equilibria (NE) of the price and quality games and the market entry barrier for each WSP.…”
Section: Wi-fi Like Servicementioning
confidence: 99%
“…However, they assumed that the spectrum leasing cost is constant and does not depend on the total demand in the spectrum auction. Kasbekar et al [14] considered a hierarchical game of quantity-price competition, with a two-level prioritized service available to the end-users, and Kasberkar and Sarkar [15] analyzed the case where the availability of licensed channels is determined with some probability while no channel-state transition occurs during a lease term. None of the above work, however, considered time-varying spectrum availability, while assuming that a leased channel is always idle during a leasing term.…”
Section: Related Workmentioning
confidence: 99%
“…Zhu et al [14] introduced a hierarchical spectrum market with spectrum brokers and secondary service providers, where dynamic spectrum leasing and service selection are investigated. Kasbekar et al [18] considered a hierarchical game between two spectrum market layers, and analyzed the interaction between the regulator, service providers and mobile subscribers.…”
Section: Related Workmentioning
confidence: 99%
“…In [5], large population minority games are studied from a statistical mechanics viewpoint in the context of financial markets. In [6], mobile subscribers are modeled as a continuum, and it is shown that a thresholdtype Wardrop equilibrium exists as a result of competitions for users between two base stations. In [10], the concept of oblivious equilibrium is proposed for the analysis of a class of large-scale stochastic games.…”
Section: Introductionmentioning
confidence: 99%